Managing maternal and child health programmes a practical guide. (Manila World Health Organization, Regional Office for the Western Pacific, 1997)
This publication intends to help managers of health services ensure that good quality maternal and child health, and family planning care are provided to all in need of such care. The World Health Organization aims to improve the reproductive health of mothers and children of developing countries by using this publication as a guide. This guide includes management, planning, organization, monitoring and supervising of maternal and child health activities.
Keywords: Maternal health services -- Handbooks, manuals, etc; Child health services -- Handbooks, manuals, etc; Health services administration